Thousand words about cervical cancer and epigenetics - Bronowicka-Kłys, Dorota Ewa; Pawlik, Patrycja; Jagodziński, Paweł Piotr (Journal of Medical Science, 2016)
Epigenetic modifications include DNA methylation, DNA demethylation along with the major role fulfilled by TET protein. Epigenetic modifications refer to the regulation of gene expression without the alteration of the DNA sequence. Some of the most common epigenetic modifications include DNA methylation and demethylation, as well as the functional role of TET proteins. Epigenetic alterations are heritable traits, therefore one of the key elements to understanding the mechanisms of cancer development is to further our knowledge on the role and function of epigenetic modifications.This mini-review takes into consideration the overview of the literature on the impact of epigenetic changes in cancer development, especially in the development of CC. Researchers believe that certain compounds are capable of inhibiting the process of DNA methylation and may play an important role in future cancer therapy.
Keywords: cervical cancer; epigenetic; DNA methylation; TET